Implementasi Pendidikan Lintas Budaya dan Relevansinya dengan Kurikulum Merdeka di SMA 1 Polewali - Akbar, Aidul; Najamuddin, Najamuddin; Alwi, Alimin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Indonesia boasts a diversity of backgrounds, social, cultural, biological, and religious backgrounds. For the nation's progress, this diversity can be a source of character values. However, if not handled properly, it can also trigger conflict. Therefore, multicultural education must be instilled from an early age. Multicultural education can be taught in elementary schools. This study examined the implementation of multicultural education and its application to the autonomous curriculum at SMA Negeri 1 Polewali. Documents, observations, and interviews were used to collect data. The data were reviewed after data collection, data reduction, data presentation, and conclusion drawing. Based on the study's findings, SMA Negeri 1 Polewali students are inclusive and diverse. Educators have responded to this diversity by offering a variety of extracurricular activities and using various learning strategies in the classroom. P5 is implemented with the theme of Diversity. Through these aspects, it can be seen that the instillation of multicultural education at SMA Negeri 1 Polewali is not manifested in specific multicultural subjects but in the various activities carried out at the school. This program is also part of the implementation of the Independent Curriculum. Therefore, it can be concluded that the implementation of multicultural education at SMA Negeri 1 Polewali is relevant to the Independent Curriculum.